2012
DOI: 10.1038/jp.2012.2
|View full text |Cite
|
Sign up to set email alerts
|

Severe maternal and perinatal outcomes from uterine rupture among women at term with a trial of labor

Abstract: Objective: To describe maternal and perinatal morbidity and mortality associated with uterine rupture (UR) among women with prior cesarean/s, singleton term pregnancies and a trial of labor after cesarean (TOLAC).Study Design: Linked hospital discharge files and birth/fetal death certificates identified potential cases of UR in Massachusetts from 1990 to 1998 with definitive identification by medical record abstraction.Result: Among the 347 identified URs, severe outcomes occurred in 86 cases (25%), in 49 (14%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 17 publications
(13 reference statements)
1
13
2
Order By: Relevance
“…The level of obstetric intervention during TOLAC is an important consideration in the hospital context as well . It is well known that uterine rupture and its consequences are significantly less likely to occur in a spontaneous labor that progresses normally to a vaginal birth . However, women attempting a TOLAC in US hospitals are often confined to bed with continuous fetal monitoring, intravenous fluids, oxytocin (Pitocin) augmentation, and other obstetric interventions .…”
Section: Birth Site Considerations For Trial Of Labor After Cesareanmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of obstetric intervention during TOLAC is an important consideration in the hospital context as well . It is well known that uterine rupture and its consequences are significantly less likely to occur in a spontaneous labor that progresses normally to a vaginal birth . However, women attempting a TOLAC in US hospitals are often confined to bed with continuous fetal monitoring, intravenous fluids, oxytocin (Pitocin) augmentation, and other obstetric interventions .…”
Section: Birth Site Considerations For Trial Of Labor After Cesareanmentioning
confidence: 99%
“…22 It is well known that uterine rupture and its consequences are significantly less likely to occur in a spontaneous labor that progresses normally to a vaginal birth. 19,62 However, women attempting a TOLAC in US hospitals are often confined to bed with continuous fetal monitoring, intravenous fluids, oxytocin (Pitocin) augmentation, and other obstetric interventions. 9,13 In the course of counseling, providers have a key role in educating women about the relationship between physiologic management practices, TOLAC safety, and VBAC success.…”
Section: Level Of Obstetric Interventionmentioning
confidence: 99%
“…Several studies examined interbirth interval (rather than interpregnancy interval), [43][44][45][46][47][48][49][50][51][52][53] presented crude results only (no adjustment for maternal age), 22,43,49,52,54,55 or did not account for a potential non-linear relationship between interpregnancy interval and health outcome by either assuming that interpregnancy interval had a linear association with risks of adverse outcomes or using a reference category with no upper bound. 20,22,46,47,[56][57][58] Nevertheless, the conclusions of the excluded studies are consistent with our findings that short interpregnancy interval is associated with increased risk of uterine rupture among women with prior caesarean birth 46,47,49 and placental abruption, 17,52 as well as decreased risk of preeclampsia or other hypertensive disorders of pregnancy. 12,21,50,51,59,60 However, in contrast to the studies in our review, several excluded studies suggested that risks of obesity and gestational diabetes may actually increase with longer (not shorter) interpregnancy interval.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure for final study selection is shown in Figure . After careful assessment, only 15 studies were eligible for the systematic review, including 10 cohort studies , 1 cross‐sectional study, and 4 case–control studies …”
Section: Resultsmentioning
confidence: 99%